Imagens de escola: é possível fabular o vazio? - Roseiro, Steferson Zanoni (2023)
Proposing to tear apart the images of schools in fabulations empty of meaning, the thesis questions: first the colors or the aches? The research was developed with fabulation as the specific methodology of cartography, and involved children from Elementary School of a public school of Espírito Santo. To register this research, the children created drawings and paintings and occasional written records. Defending the thesis that, in order to outline other possibilities for school, it is necessary to tear the images of schools empty enough for other experiences of the body to emerge from there from there in time, the writing begins by claiming to point out the close alliance between curriculum and the function of school. Thus, it understands curriculum as actions that bring together, at school, the body of knowledge and the knowledge of the world, producing in the first a feeling of continuity with the second. Aware of the dangers of a continuity that doesn’t confront capitalistic machinery, the thesis seeks to produce images of school beyond the pimping of life. In this way, students invite the school to think about the body in curricular exercises. They paint courts and give rise to gossip as attempts to provoke perceptual openings in time. At the end, the thesis deals precisely with fabulating meanings of school from empty spaces. Exercising fabulation requires a lot of perceptual openness from the body; sensitivity to time; and the certainty that no one fabulates alone.